Risk assessment on offshore photovoltaic power generation projects in China based on a fuzzy analysis framework. (1st April 2019) - Wu, Yunna; Li, Lingwenying; Song, Zixin; Lin, Xiaoshan
Abstract: China has begun to promote offshore photovoltaic in coastal areas taking its advantages of saving land resources and proximity to load centers. However, the projects are bound to face a series of risk factors as the industry is in its infancy. This paper conducts a risk assessment on offshore photovoltaic power generation projects in China based on a fuzzy framework. Firstly, 16 risk factors affecting offshore photovoltaic power generation projects in China are identified and classified into 4 groups. Secondly, a risk assessment model is constructed involving Hesitant Fuzzy Linguistic Term Sets, Triangular Fuzzy Number and Fuzzy Synthetic Evaluation. Thirdly, this paper conduct an empirical study of China, and the result shows that the risk level of offshore photovoltaic power generation projects in China is medium high. Finally, some response measures are proposed. The risk index system and corresponding countermeasures can provide a reference for project managers to allocate resources to prevent risk events. Besides, the risk assessment model can help project investors to avoid too risky projects. In addition, the risk assessment on offshore photovoltaic power generation projects in China has not been discussed by scholars yet. Thus, this paper contributes to the literature and expand the knowledge. Highlights: An index system is established for risk assessment on offshore photovoltaic power generation projects. A risk assessment model is put forward based on fuzzy theories. Correlations between criteria are analyzed to construct the analytic network process structure. An empirical study of China is conducted. Effective response strategies are proposed towards each risk.